Intuitive eating Scale-2: Factor structure and associations with disordered eating, impulsivity and quality of life in adolescents with overweight/obesity - Ramalho, Sofia Marlene Marques (2022)
Objective: The Intuitive Eating Scale-2 (IES-2) has been shown to be a valid tool to assess the capability of eating in reaction to natural hunger/satiety cues. However, its factor structure seems to differ in function of cultural/socioeconomic backgrounds, and its psychometric properties among the adolescents with overweight/obesity (BMI-for-age percentile >85th) have not been examined yet. Thus, this study aims to 1) investigating the factorial structure/psychometric properties of IES-2 in adolescents with overweight/obesity; and 2) exploring the associations between impulsivity, quality of life disordered and intuitive eating. Methods: A total of 202 Portuguese adolescents (124 girls; 78 boys; 12–19 years) under weight-loss treatment with a mean BMI z-score of 2.41 (SD = 0.75) participated in this study. The IES-2 factor structure was explored by confirmatory factor analysis and bifactor models. Test-retest reliability analyses were performed over 6 months (n = 41) and associations between the variables under study were explored. Results: Confirmatory factor analyses with posthoc modifications resulted in a bifactor model with acceptable fit supporting one general factor (intuitive eating) and three specific factors (IES-2 subscales). The “Unconditional Permission to Eat” subscale could not be replicated in this sample. Test-retest reliability analyses suggested good temporal stability. Intuitive eating scores were negatively associated with grazing eating behavior and impulsivity (negative urgency) and positively linked to quality of life. Conclusions: An adjusted version of IES-2 can be an appropriate measure for assessing intuitive eating levels in adolescents with overweight/obesity. Research on intuitive eating has the potential to enhance pediatric weight-loss interventions.